Spirit Tech: The Brave New World of Conscious Hacking and Enlightenment Engineering. - Van Eyghen, Hans (Zygon: Journal of Religion & Science, 2022)
The discussion on technologies that tamper with the human brain are well embedded in data from cognitive neuroscience regarding how the human brain works and processes information. Wesley Wildman and Kate Stockly present a fascinating overview of new "religious technologies". Although the goals or results differ, all technologies allow humans to go where normal, non-enhanced human minds cannot go.